Information Technology Capabilities Enhance Business Performance: The Role of Organisational Agility, Ambidexterity, and Regulatory Support - Hoa D.X. Trieu,; Phuong V. Nguyen,; Khoa T. Tran, (Asian Academy of Management Journal, 2025)
In pursuing a market position, enterprises have increasingly turned to information technology (IT) to help improve their performance. Our research assesses the influence of IT capabilities as a strategic resource for business performance within the context of dynamic capabilities theory. It also examines the mediating role of organisational ambidexterity and agility in the relationship between IT capabilities and business performance, thereby shedding light on the mechanisms through which IT capabilities impact overall organisational success. The role of regulatory support in digital transformation is also investigated. This paper uses Partial Least Squares Structural Equation Modelling to analyse 321 respondents from Vietnamese enterprises. The results highlight the mediating effects of organisational agility and ambidexterity on the relationship between IT capabilities and business performance. These findings confirm that regulatory support moderates the association between organisational ambidexterity and business performance. Limitations and future research directions are discussed in the paper as well.